A study on non-healing plantar diabetic foot ulcers to assess the effect of compliance of using customised footwear in wound healing - Someshwara Rao, Pallela Narayana; Vincent, Anil Vince (International Surgery Journal, 2020)
Background: Foot infection is one of the commonest reasons for hospital admission of individuals with diabetes in India. Prescription footwear is an intricate aspect of a treatment program, not a therapy unto itself. Custom-made footwear can only be effective in preventing diabetic foot ulcers if worn by the patient as advised. This study was done in patients who are already prescribed customised footwear and evaluated the need for compliance based on the healing of these plantar foot ulcers. Methods: 85 diabetic patients with severe neuropathy and a non-healing callus ulcer or trophic ulcer (diameter 1-3 cm) for more than 3 months were included in the study. All these patients were followed up on weekly basis for 3 months and questioned about the use of customized footwear on regular basis. At the end of three months, the healing of these foot ulcers was compared based on whether they had been compliant with the customized footwear advice. Results: Of the 85 patients, 25 (29.4%) had shown improvement in wound healing with regular use of footwear. 60 (70.5%) patients who were not using the customized footwear had not shown any improvement in the plantar ulcers. The reasons for not using the recommended footwear were many commonest being wearing footwear only when going out and not inside the home. Conclusions: Non-compliance with customised footwear is emerging as an important cause of delay in wound healing of plantar foot ulcers.